Mapping and characterization of the major quantitative trait locus qSS7 associated with increased length and decreased width of rice seeds - Xianjin Qiu; Rong Gong; Youbin Tan; Sibin Yu (Theoretical and Applied Genetics, 2012)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Protective roles of quercetin in acute myocardial ischemia and reperfusion injury in rats - Hong-Bo Jin; Yong-Bin Yang; Ying-Li Song; Yong-chun Zhang; Yu-Rong Li (Molecular Biology Reports, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Magma mingling and chemical diffusion in the Taojiang granitoids in the Hunan Province, China: evidences from petrography, geochronology and geochemistry - Kai-Xing Wang; Pei-Rong Chen; Wei-Feng Chen; Hong-Fei Ling; Kui-Dong Zhao; Zhi-Qiang Yu (Mineralogy and Petrology, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Protective effect of whey protein hydrolysates against hydrogen peroxide-induced oxidative stress on PC12 cells - Qiu-Xiang Zhang; Yu-Fang Ling; Zhen Sun; Li Zhang; Hui-Xin Yu; Samuel Mburu Kamau; Rong-Rong Lu (Biotechnology Letters, 2012)

Enhanced apoptosis in retinal pigment epithelium under inflammatory stimuli and oxidative stress - Yujuan Wang; Defen Shen; Vinson M. Wang; Cheng-Rong Yu; Ren-Xi Wang; Jingsheng Tuo; Chi-Chao Chan (Apoptosis, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

The contribution of intersubspecific hybridization to the breeding of super-high-yielding japonica rice in northeast China - Jian Sun; Di Liu; Jia-Yu Wang; Dian-Rong Ma; Liang Tang; Hong Gao; Zheng-Jin Xu; Wen-Fu Chen (Theoretical and Applied Genetics, 2012)

Multiple time scale characteristics of rainfall and its impact on soil salinization in the typical easily salinized area in Huang-Huai-Hai Plain, China - Shi-Peng Yu; Jing-Song Yang; Guang-Ming Liu; Rong-Jiang Yao; Xiang-Ping Wang (Stochastic Environmental Research and Risk Assessment, 2012)

Relationships between hemorrhage, angioarchitectural factors and collagen of arteriovenous malformations - Hongchuan Niu; Yong Cao; Xuejiang Wang; Xiaowei Xue; Lanbing Yu; Ming Yang; Rong Wang (Neuroscience Bulletin, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Rice choline monooxygenase (OsCMO) protein functions in enhancing glycine betaine biosynthesis in transgenic tobacco but does not accumulate in rice (Oryza sativa L. ssp. japonica) - Di Luo; Xiangli Niu; Jinde Yu; Jun Yan; Xiaojun Gou; Bao-Rong Lu; Yongsheng Liu (Plant Cell Reports, 2012)

Synthesis and anticonvulsant activity of 8-alkoxy-5,6-dihydro-4H-benzo[f][1,2,4]triazolo[4,3-a]azepine derivatives - Wen-Bin Zhang; Rong-Bi Han; Wei Zhang; Ri-Shan Jiang; Feng-Yu Piao (Medicinal Chemistry Research, 2012)

Impact of nodular size on the predictive values of gray-scale, color-Doppler ultrasound, and sonoelastography for assessment of thyroid nodules - Yu-rong Hong; Yu-lian Wu; Zhi-yan Luo; Ning-bo Wu; Xue-ming Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Association between SHBG Asp327Asn (rs6259) polymorphism and breast cancer risk: a meta-analysis of 10,454 cases and 13,111 controls - Jue-Yu Zhou; Rong Shi; Hai-Lang Yu; Wen-Ling Zheng; Wen-Li Ma (Molecular Biology Reports, 2012)

A new phenylalkanoid from the rhizomes of Zingiber officinale - Soong-Yu Kuo; Rong-Jyh Lin; Yu-Ting Yeh; Jun-Yen Lee; Chung-Yi Chen (Natural Product Research, 2012)

Molecular identification and antibiotic control of endophytic bacterial contaminants from micropropagated Aglaonema cultures - Jong-Yi Fang; Yu-Rong Hsu (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Interactions between CYP1A1 polymorphisms and cigarette smoking are associated with the risk of hepatocellular carcinoma: evidence from epidemiological studies - Lei Yu; Lei Sun; Yang-Fang Jiang; Bao-Ling Lu; De-Rong Sun; Li-Ying Zhu (Molecular Biology Reports, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

Characterization of the role of protein–cysteine residues in the binding with sodium arsenite - Yu-Ying Chang; Tai-Chih Kuo; Chun-Hua Hsu; Duen-Ren Hou; Yung-Hsi Kao; Rong-Nan Huang (Archives of Toxicology, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

Toxicity of profenofos to the springtail, Folsomia candida, and ammonia-oxidizers in two agricultural soils - Yu-Rong Liu; Yuan-Ming Zheng; Ji-Zheng He (Ecotoxicology, 2012)

Genetic diversity of four new species related to southwestern Sichuan buckwheats as revealed by karyotype, ISSR and allozyme characterization - Mei-Liang Zhou; Da-Quan Bai; Yu Tang; Xue-Mei Zhu; Ji-Rong Shao (Plant Systematics and Evolution, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Influence of education and working background on physicians’ knowledge of secondary prevention guidelines for coronary heart disease: results from a survey in China - Yan-jun Gong; Tao Hong; Jie Jiang; Rong-hui Yu; Yan Zhang; Zhao-ping Liu; Yong Huo (Journal of Zhejiang University-SCIENCE B, 2012)

Functional analysis of the HS185 regulatory element in the rice HSP70 promoter - Yu-Man Zhang; Yu-Mei Zheng; Na Xiao; Li-Na Wang; Yao Zhang; Rong-Xiang Fang; Xiao-Ying Chen (Molecular Biology Reports, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

Occupational risks and lung cancer burden for Chinese men: a population-based case–referent study - Lap Ah Tse; Ignatius Tak-sun Yu; Hong Qiu; Joseph Siu Kai Au; Xiao-rong Wang (Cancer Causes & Control, 2012)